Acupuncture as a multifunctional neuroprotective therapy ameliorates cognitive impairment in a rat model of vascular dementia: A quantitative iTRAQ proteomics study. (2nd October 2018) - Yang, Jing‐Wen; Wang, Xue‐Rui; Zhang, Meng; Xiao, Ling‐Yong; Zhu, Wen; Ji, Cai‐Shuo; Liu, Cun‐Zhi
Summary: Aims: Acupuncture has been reported to affect vascular dementia through a variety of molecular mechanisms. An isobaric tag for relative and absolute quantification (iTRAQ) with high‐resolution liquid chromatography‐tandem mass spectrometry (LC‐MS/MS) analyses makes it possible to attain a global profile of proteins. Hence, we used an iTRAQ‐LC‐MS/MS strategy to unravel the underlying mechanism of acupuncture. Methods: Wistar rats were subjected to vascular dementia with bilateral common carotid occlusion. Acupuncture was intervened for 2 weeks at 3 days after surgery. The Morris water maze was used to assess the cognitive function. Proteins were screened by quantitative proteomics and analyzed by bioinformatic analysis. Four differentially expressed proteins (DEPs) were validated by western blot. The reactive oxygen species (ROS) production, neuron cell loss, and long‐term potentiation (LTP) were determined after western blot. Results: Acupuncture at proper acupoints significantly improved cognitive function. A total of 31 proteins were considered DEPs. Gene ontology (GO) analysis showed that most of the DEPs were related to oxidative stress, apoptosis, and synaptic function, which were regarded as the major cellular processes related to acupuncture effect. Western blot results confirm the credibility of iTRAQ results. Acupuncture could decrease ROS production, increase neural cell survival, and improve LTP, which verified the three major cellular processes. Conclusion: Acupuncture may serve as a promising clinical candidate for the treatment of vascular dementia via regulating oxidative stress, apoptosis, or synaptic functions.